An Algerian perspective on non-typhoidal Salmonella infection - Bilal Djeghout; Ammar Ayachi; Bianca Paglietti; Gemma C. Langridge; Salvatore Rubino (Journal of Infection in Developing Countries)
Non-typhoidal Salmonella (NTS) represents a leading cause of food-borne disease worldwide. It is a global public health concern: more than 94 million cases and 115,000 deaths are reported every year, with a disproportionate impact in developing countries. The prevalence of multi-drug-resistant (MDR) Salmonella strains is another major health concern which affects antimicrobial treatment, as many studies report that infections caused by MDR strains are more severe than those caused by susceptible strains. In Algeria, NTS represent one of the primary causes of salmonellosis in both humans and food animal production, especially poultry. Epidemiological surveillance systems and monitoring programs for Salmonella infections are essential requirements to provide data useful for the effective detection and control of Salmonella outbreaks. The present review will supply a perspective on NTS infection, pathogenesis and antimicrobial resistance with a focus on the epidemiology of salmonellosis in Algeria.